Employee Performance Model: Implementation of Work Environment Work Discipline and Competence - Lokot Muda Harahap (CERED Indonesia Institute, 2021)
This research was conducted on employees of Bank Bukopin's Setia Budi Medan Branch Office in the staffing section with a population of 106 employees. The sampling technique used purposive sampling method and the research sample obtained was 42 respondents. The method used is a quantitative research method. This study uses instrument tests (validity test and reliability test), data analysis techniques (classical assumption test: multicollinearity test, heteroscedasticity test, and normality test), multiple linear regression test, Coefficient of Determination test (D), hypothesis test (partial t test and simultaneous f test). Meanwhile, for data processing using SPSS for Windows Realease 21.0 program. Based on the results of this study, the work discipline variable is a variable that has a dominant influence on employee performance variables at Bank Bukopin employees at the Setia Budi Branch Office (KCP). It is proven by the results of the t-test that the variables of work environment, work discipline, and compensation have a significant effect on employee performance. The results of the statistical t-test of the work environment variables t arithmetic > t table are: (3.120 > 2.024), the work discipline variable is: (2.306 > 2.024), while the compensation variable has a value (4.181 > 2.024). The results of the F test can be concluded that there is a simultaneous and significant effect between the variables of work environment, work discipline, and compensation on employee performance. The result of the calculated F test is greater than the F table value (58.449 > 4, 066) with a probability less than 0.05 (0.000 < 0.05). The results obtained by the coefficient of determination or (R2) of 0.808. This means that 80.8% of the variation of changes in employee performance ups and downs is due to changes in work environment variables, work discipline, compensation. While the remaining 19.2% was caused by other factors that were not analyzed in the model used in the study.